Natural Surfactant from Fatty Acid of Morinda citrifolia L. for Deinking Flotation - Trismawati Trismawati; I.N.G. Wardana; Nurkholis Hamidi; Mega Nur Sasongko (ASEAN Journal of Chemical Engineering, 2017)
Natural surfactant is developed as fatty acid derivate from natural resources such as palm oil, sunflower oil, and safflower oil. In South East Asia countries, the palm oil is used as the main resources of fatty acid derivate. Seed oil of Morinda citrifolia L. contains unsaturated fatty acid. It is extracted and concentrated. The concentrated fatty acid of Morinda citrifolia L. (CFAMC) is used as deinking surfactant. The CFAMC is analyzed by GCMS for its constituent and its deinking flotation performance is evaluated for yield, brightness, and ERIC of deinked pulp. Based on the old newspaper (ONP) pulp with brightness of 35.84 °ISO, and ERIC of 1982.4 ppm, the deinking flotation performance of CFAMC is approaching the natural surfactant. The brightness increase is 11.36% and 16.35%, and the ERIC reduction is 37.40% and 47.73% for CFAMC and natural surfactant respectively. SEM analysis is provided to see the residual Nanoink particles on the fibers.